NEW VIDEO COMPRESSION USING MSPIHT3D - ZITOUNI, A.; TALEB AHMED, A.; OUAFI, A.; BAARIR, Z.; KHELIFA, A. (Courrier du Savoir; Vol. 19 (2015): COURRIER DU SAVOIR(Mars), 2015)
ABSTRACT In this paper, we propose a new approach to video compression based on the principle of Set Partitioning In Hierarchical Tree algorithm (SPIHT). Our approach, the modified SPIHT3D (MSPIHT3D), distributes entropy differently than SPIHT3D and also optimizes the coding. This approach can produce results that are a significant improvement on the Peak Signal-to-Noise Ratio (PSNR) and compression ratio obtained by SPIHT3D algorithm, without affecting the computing time. KEYWORDS: video compression,, MSPIHT3D, arithmetic Coding, PSNR, Compression ratio.